2003
DOI: 10.1021/jp0351223
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Aluminum Chloride Activation for Toluene Chlorination

Abstract: Aluminum chloride, in the absence of solvent and moisture, was observed to exert a negligible catalytic effect upon the chlorination of toluene, but in the presence of atmospheric moisture, a very large catalytic effect was evident. DFT calculations were performed on a number of possible intermediates involved in the chlorination process. The calculations suggest that dimeric aluminum chloride predominates in the absence of solvents or moisture, and it is not active as a catalyst. It is suggested that HCl is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…72 We have found that BF 4 − and AlCl 4 − anions are suitable counterions, which can effectively stabilize σ-complex C 6 H 5 Cl + (Figure 2). It is in agreement with analogous results from molecular orbital studies of chlorination of toluene 5 and benzene 6 catalyzed by AlCl 3 . These computational results indicate that not only is the reaction rate increased with Lewis acid catalyst but also the general mechanism of the aromatic chlorination is changed.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…72 We have found that BF 4 − and AlCl 4 − anions are suitable counterions, which can effectively stabilize σ-complex C 6 H 5 Cl + (Figure 2). It is in agreement with analogous results from molecular orbital studies of chlorination of toluene 5 and benzene 6 catalyzed by AlCl 3 . These computational results indicate that not only is the reaction rate increased with Lewis acid catalyst but also the general mechanism of the aromatic chlorination is changed.…”
Section: Resultssupporting
confidence: 90%
“…We have found that BF 4 – and AlCl 4 – anions are suitable counterions, which can effectively stabilize σ-complex C 6 H 5 Cl + (Figure ). It is in agreement with analogous results from molecular orbital studies of chlorination of toluene and benzene catalyzed by AlCl 3 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…riedel-Crafts reactions have been the topic of the numerous experimental [1] and theoretical [2][3][4][5] studies. In our recent report [6] we tested several computational approaches to describe the thermodynamics of such reactions and found that molecules containing dimeric form of the metal halides may be important intermediates.…”
mentioning
confidence: 99%
“…In recent decades, experimental reports on chlolo-substitution mechanism of aromatic compounds [5] have put forward that positive-charged Cl δ+ is the electrophilic reagent in the reaction. Meanwhile, theoretical studies since the 1960s were only related to solvent effect on the chloro-substitution reaction rate and the catalysis of AlCl 3 in toluene ring chlorination [6][7][8][9][10]. According to the co-effect of conjugation and electron donating inductivity of methyl, its para-and ortho-ring hydrogens are preferred ones for chloro-substitution, which results in the predominance of OCT and PCT over MCT.…”
Section: Introductionmentioning
confidence: 99%